Modern Trends of Internet Banking Market in Supply Chain of Russia - Lilia M. Yusupova; Tatyana V. Nikonova; Irina A. Kodolova; Railia R. Kalimullina (International Journal of Supply Chain Management, 2018)
Nowadays modern economic system and banking system in particular is defined as a globally developed and integrated system. Internet banking gained particular interest as a kind of remote banking, which is the most progressive direction of banking system development. It is one of the most dynamic and rapidly developing sectors of the e-Commerce market. The issues of strategic development determine the interest, attracted to the development of internet banking. Practice shows that investments in such projects begin to make a profit only after a certain period of time necessary for training and adapting the system to specific conditions. Investing in software, computer and telecommunications equipment and creating a base for the transition to new computing platforms, provide banks with ability to reduce the cost of services, accelerate the payments transactions through the banking system and reduce the complexity of banking services. The largest banks provide the richest set of internet banking services abroad. Internet banking in supply chain of Russia is at the stage of formation. In order to reach the modern level of development of the banking sector, it is essential for supply chain of Russia to form a national market for internet banking. The development of remote banking services based on Internet banking technology will give a new impetus to the development of electronic banking services in banking.